Changes to Material Phase and Morphology Due to High-Level Molybdenum Doping of ZnO Nanorods: Influence on Luminescence and Defects - Buryi, Maksym; Babin, Vladimir; Neykova, Neda; Wang, Yu-Min; Remeš, Zdeněk; Ridzoňová, Katarína; Dominec, Filip; Davydova, Marina; Drahokoupil, Jan; Chertopalov, Sergii; Landová, Lucie; Pop-Georgievski, Ognen (Materials (Basel, Switzerland), 2023)
The influence of Mo on the electronic states and crystalline structure, as well as morphology, phase composition, luminescence, and defects in ZnO rods grown as free-standing nanoparticles, was studied using a variety of experimental techniques. Mo has almost no influence on the luminescence of the grown ZnO particles, whereas shallow donors are strongly affected in ZnO rods. Annealing in air causes exciton and defect-related bands to drop upon Mo doping level. The increase of the Mo doping level from 20 to 30% leads to the creation of dominating molybdates. This leads to a concomitant drop in the number of formed ZnO nanorods.
Keywords: luminescence; electron paramagnetic resonance; morphology; ZnO nanorods; molybdenum doping